Evaluación de la susceptibilidad a glicopéptidos en cepas de Staphylococcus aureus resistentes a oxacilina - Castellano-González Maribel; Perozo-Mena Armindo; González Ana Isabel (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Abstract: The decrease in susceptibility to glycopeptides by oxacillin resistant Staphylococcus aureus (ORSA) has become a current problem. Objective: To evaluate susceptibility to glycopeptides in ORSA strains isolated in the University Hospital, Maracaibo, during the first quarter of 2010. Methods: Oxacillin resistance of the ORSA strains was verified by diffusion on agar (oxacillin 1 µg and cefoxitin 30 µg, OXOID®), a screening test in Müeller Hinton agar with 6 µg/mL of vancomycin (Sigma®), and E-test® for minimum inhibitory concentration (MIC) for oxacillin, detection of PBP2a (Latex, OXOID®) and the mecA gene by polymerase chain reaction (PCR). In addition, susceptibility to glycopeptides was determined by disk diffusion (teicoplanin, 30 µg OXOID®), MIC by E-test®, screening test in Müeller-Hinton agar with teicoplanin (5 µg/ml) or in brain heart infusion agar with vancomycin (6 µg/mL), glycopeptide hetero-resistance detection by GDR E-test® and detection of the vanA gene using PCR. Results: No ORSA strain was isolated with intermediate resistance (VISA or hVISA), nor with high-level resistance to glycopeptides. Conclusions: Locally, there is no incidence of ORSA strains resistant to glycopeptides; therefore, these antibiotics continue to be useful for treating infections produced by this important pathogen. Resumen: La disminución de la susceptibilidad a los glicopéptidos por parte de Staphylococcus aureus oxacilina resistente (SAOR) se ha convertido en una problemática actual. Objetivo: Evaluar la susceptibilidad a los glicopéptidos en cepas SAOR aisladas en el Hospital Universitario de Maracaibo, durante el primer trimestre del 2010. Métodos: a las cepas SAOR se le verificó la resistencia a oxacilina por difusión en agar (oxacilina 1 µg y cefoxitina 30 µg, OXOID®), prueba de descarte en agar Müeller Hinton con 6 µg/mL de oxacilina (Sigma®), concentración inhibitoria mínima (CIM) a oxacilina mediante E-test®, detección de PBP2a (látex, OXOID®) y del gen mecA por reacción en cadena de la polimerasa (PCR). Se determinó, además, la susceptibilidad a glicopéptidos por difusión del disco (teicoplanina 30 µg, OXOID®), CIM por E-test®, prueba de descarte en agar Müeller-Hinton con teicoplanina (5 µg/mL, Sigma®) o infusión cerebro corazón con vancomicina (6 µg/mL, Sigma®), detección de hetero-resistencia (GDR E-test®) y la detección del gen vanA mediante PCR. Resultados: no se aisló ninguna cepa SAOR con resistencia intermedia (VISA o hVISA), ni tampoco, con resistencia de alto nivel a glicopéptidos (SAVR). Conclusiones: En la localidad, no existe incidencia de cepas SAOR resistentes a los glicopéptidos, por lo que estos antibióticos continúan siendo de utilidad en la terapéutica de las infecciones producidas por este importante patógeno.